The potential of miR-29 in modulating tumor angiogenesis: a comprehensive review - Rui-Ting Zhou; Xiao-Jie Luo; Xiao-Xin-Ran Zhang; Jiang-Feng Wu; Yi-Ran Ni (Discover Oncology, 2025)
Abstract MicroRNAs (miRNAs) are a class of short non-coding RNAs that play a crucial role in the post-transcriptional regulation of gene expression. They are associated with various biological processes related to tumors. Among the numerous miRNAs, miR-29 has garnered attention for its role in regulating tumor angiogenesis. In numerous human tumors, miR-29 has been demonstrated to negatively correlate with the capacity for angiogenesis and the degree of malignancy, as well as with the expression levels of pro-angiogenic factors such as vascular endothelial growth factor vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), and matrix metalloproteinase (MMP)-2. Multiple studies, utilizing techniques like dual-luciferase reporter assays, have confirmed that miR-29 directly targets the 3'-untranslated region (UTR) of mRNAs for VEGF, PDGF, and MMP-2. Extensive investigations involving tumor cell lines and animal models have shown that the overexpression of miR-29, achieved through miRNA transfection or the introduction of miRNA mimics, effectively inhibits angiogenesis by upregulating these pro-angiogenic factors. Conversely, downregulation of miR-29 using specific inhibitors promotes angiogenesis. While small molecule inhibitors and antibodies targeting VEGF constitute a primary strategy in anti-angiogenesis therapies, miR-29's ability to target multiple pro-angiogenic molecules positions it as a promising candidate for future therapeutic interventions, especially with ongoing advancements in nucleic acid drug design and delivery systems.